Outcome of Different Endoscopic Modalities in Management of Large Proximal Ureteric Stone - Ali, S M Yunus; Islam, Md. Saiful; Islam, Md. Saiful; Jahan, Salma; Islam, Mohammed Rafiqul; Miraj, A. K. Al (International Journal of Medical Research and Review, 2025)
Background: A urologist inserts a long, thin tube with a camera (ureteroscope) into your urethra (where pee leaves your body). They feed the ureteroscope through your bladder and into your ureter. Once they find your stone, they remove it or break it up with a laser. Percutaneous nephrolithotomy. Various techniques have been documented for the management of Large Proximal Ureteric Stones (LPUS), such as laparoscopy (LUL), antegrade approach, retrograde ureteroscopy (RURS), extracorporeal shockwave lithotripsy, and infrequently open surgery. The paper aimed to compare the overall results of treating patients with large proximal ureteric stones (15-20 mm) using transperitoneal LUL, RURS, and mini-percutaneous antegrade ureteroscopy. Methods: This prospective, randomized trial involved 100 individuals of both sexes who were above the age of 18 and had a single, 15-20 mm LPUS. Patients were split into two equal groups at random: Group B received RURS combined with laser fragmentation, and Group A received LUL. Results: 100 patients who were included in the trial were split evenly between the two groups based on similar demographic information and stone criteria. Regarding patient demographics and stone criteria, both groups were similar. Group A had a substantially greater stone-free percentage (100%) than Group B (72%). There was a significant difference (p<0.001) in the operating duration, hemoglobin deficit, and ultimate stone-free rate between groups A and B. There was little difference in the two groups’ conversation rates, mucosal injuries, ureteral perforations, complications, and length of hospital stay. Conclusions: Compared to RURS, LUL is linked to a greater stone-free rate and fewer complications.